Building Windows 8 apps with C♯ and XAML - Likness, Jeremy (Microsoft Windows development series., 2012)
"Jeremy builds real apps for real customers. That's why I can heartily recommend this book. Go out and write some great apps ... and keep this book handy."--The Foreword by Jeff Prosise. Build Exceptionally Immersive and Responsive Touch-Based Windows Store Apps for Windows 8 with C# and XAML. This is the first practical guide to building breakthrough applications for Windows 8 from project templates through publication to the new Windows Store. Microsoft 'MVP of the Year' Jeremy Likness helps you combine your existing developer skills with new Visual Studio 2012 tools and best practices to create apps that are intuitive and innovative. His guidance and insight will help you dive into Windows 8 development - and gain a powerful competitive advantage for years to come. Likness illuminates the entire apps lifecycle, from planning and Model-View-View Model (MVVM) based design through coding, testing, packaging, and deployment. He covers both business and consumer apps, showing how Windows 8/WinRT development builds upon and contrasts with older WPF and Silverlight approaches. Using carefully crafted downloadable code examples and sample projects, Likness shows how to make the most of new platform features, including integrated social networking, search, contracts, charms, and tiles. Throughout, he addresses crucial development challenges that have only been discussed on MSDN, blog posts, and Twitter feeds - and never with this depth and clarity before. Coverage includes: Mastering real-world Windows 8 development for all devices and form factors; Understanding the new WinRT framework and the unique characteristics of Windows 8 apps; Designing apps that are faster, more responsive, do more with less, and maximize battery life; Creating exceptionally fluid interfaces with VS 2012 templates, built-in animations, and XAML; Building apps that respond consistently to multiple forms of input, including complex touch manipulations; Using contracts and charms to expose services or enable users to do so; Providing information to users through Live Tiles even when your app isn't running; Connecting your app seamlessly to multiple data sources, including social networks and cloud storage; Syndicating rich, network-based content; Using Model-View-ViewModel (MVVM); Securing Windows 8 apps through authentication and authorization; Efficiently testing, debugging, packaging, and deploying apps.